Attitudes and Motivation toward Learning the English Language among Students from Islamic Education System Background: Exploring the Views of Teachers - Ismail Sheikh Ahmad; Hazlina Abdullah; Muhammad Faizal A Ghani (Intelektual Pustaka Media Utama, 2014)
Research in the field of attitudes and motivation has increasingly investigated the nature and role of motivation in L2 learning process, and many are inspired by Canadian psychologists, Robert Gardner and Wallace Lambert [1]. However, in Malaysia, there has been only a meagre number of research that investigates teachers' perceptions on attitudes and motivation of students from religious school background. It is of great significance to explore the attitudes and motivation of these groups of students because the students appeared to be weak in the English language and they also held negative perceptions toward the language [2, 3]. The present study is needed to attain authentic information about possible connections between teachers' personal experiences, their perspectives and their practices regarding teaching and learning of students from the aforementioned background. This qualitative research study contains in-depth teacher interviews that document their personal perceptions, ways of dealing with students in the specified setting, and their suggestions on improving the attitudes and motivation of learning English for students from religious school background. Findings are presented according to the research questions intended for the study and several conclusions were drawn from the data.